Uranium processing and properties - Jackson, Mark J.; Morrell, Jonathan S. (Springer New York, 2013)
Uranium Processing and Properties describes developments in uranium science, engineering and processing and covers a broad spectrum of topics and applications in which these technologies are harnessed. This book offers the most up-to-date knowledge on emerging nuclear technologies and applications while also covering new and established practices for working with uranium supplies. The book also aims to provide insights into current research and processing technology developments in order to stimulate and motivate innovation among readers. Topics covered include casting technology, plate and sheet rolling, machining of uranium and uranium alloys, forming and fabrication techniques, corrosion kinetics, nondestructive evaluation and thermal modeling. This book also: Covers a broad spectrum of topics and applications that deal with uranium processing and the properties of uranium Offers extensive coverage of both new and established practices for dealing with uranium supplies in nuclear engineering Promotes the documentation of the state-of-the-art processing techniques utilized for uranium and other specialty metals Uranium Processing and Properties is an ideal book for process, manufacturing or researcher engineers practicing or developing techniques in the field of nuclear engineering.